PENGARUH EDUKASI BERBASIS VIDEO TERHADAP PENGETAHUAN BALUT BIDAI PERTOLONGAN PERTAMA FRAKTUR TULANG PADA MASYARAKAT DI WILAYAH KERJA PUSKESMAS POLONGBANGKENG SELATAN: The Effect of Video-Based Education on Bone Fracture First Aid Knowledge Wrap in Communities in Polongbangkeng Selatan - Dewiyanti; Kamriana; Zainuddin; Alwi; Fitria Rahmadani (LPPM STIKES Pemkab Jombang, 2023)
Introduction: Splint dressing is first aid for parts of the body that experience injuries such as broken bones by maintaining a body position using objects that can maintain a stable and comfortable position. Purpose: this study is to determine the effect of video-based education on knowledge of first aid splint dressing for bone fractures in the community in the working area of ??the Polongbangkeng Selatan Health Center, Method: using a Quasy Experimental design with a one group Pre-Post test approach which aims to identify causal relationships by involving a group. Results: the results of the analysis of the Paired T Test obtained a ? value of 0.005 ? ? (0.05). The results showed that there was an effect of video-based education on knowledge of first aid splint dressing for fractures in the working area of ??the Polongbangkeng Selatan Health Center, Takalar Regency. Conclusion: Viedo-based education and counseling materials as well as splint dressing training are able to increase first aid knowledge on bone fractures in the community in the working area of ??the South Podbangkeng Health Center, Takalar Regency.